Impairments of motor function among children with a familial risk of schizophrenia or bipolar disorder at 7 years old in Denmark: an observational cohort study. (May 2017) - Burton, Birgitte Klee; Thorup, Anne A E; Jepsen, Jens Richardt; Poulsen, Gry; Ellersgaard, Ditte; Spang, Katrine S; Christiani, Camilla Jerlang; Hemager, Nicoline; Gantriis, Ditte; Greve, Aja; Mors, Ole; Nordentoft, Merete; et al.
Summary: Background: Owing to the genetic overlap between schizophrenia and bipolar disorder, we aimed to assess domain-specific motor aberrations and disorder specificity among 7-year-old children with a familial risk of schizophrenia or bipolar disorder by comparing children in familial risk groups with each other and with children not in these risk groups. Methods: In the Danish High Risk and Resilience Study, we established a cohort of 7-year-old children with no, one, or two parents with schizophrenia or bipolar disorder in Denmark between Jan 1, 2013, and Jan 31, 2016. We matched children of parents diagnosed with schizophrenia to children of parents without schizophrenia on the basis of their home address, age, and sex. Even though we did not match children of parents with bipolar disorder directly to controls because of resource constraints, we only recruited children into the three groups who did not differ in terms of age, sex, and urbanicity. We investigated motor function in children using the Movement Assessment Battery for Children–Second Edition. Motor function raters were masked to participants' clinical risk status during assessments. We assessed the effects of familial risk group in a mixed-model analysis with repeated measures with an unstructured variance component matrix. Findings: We studied 514 children (198 [39%] children of parents with schizophrenia, 119 [23%] of parents with bipolar disorder, and 197 [38%] of parents without schizophrenia or bipolar disorder). Children of parents with schizophrenia showed impaired motor performance compared with those of parents without in the subdomains of manual dexterity (mean difference −1·42 [95% CI −2·08 to −0·77]; p<0·0001) and balance (−1·38 [–2·03 to −0·72]; p<0·0001), but not of aiming and catching (−0·39 [–0·97 to 0·19]; p=0·18). Children of parents with bipolar disorder did not show any significant difference in motor performance to children of parents without in the subdomains of manual dexterity (−0·69 [–1·44 to 0·07]; p=0·08), balance (−0·68 [–1·44 to 0·08]; p=0·08), and aiming and catching (−0·36 [–1·03 to 0·31]; p=0·29). Comparison of familial risk groups of mental disorders revealed no significant differences in the subdomains of manual dexterity (−0·74 [–1·49 to 0·02]; p=0·06), balance (−0·70 [–1·46 to 0·06]; p=0·07), or aiming and catching (−0·03 [–0·70 to 0·63]; p=0·92). Interpretation: Motor abnormalities in children with a familial risk of schizophrenia are specific at 7 years of age with respect to fine motor function and balance, but non-specific with respect to familial risk of bipolar disorder. Clinicians should be aware of motor symptoms and refer children with definite motor problems (below the fifth percentile) to a child physiotherapist. Funding: Mental Health Services of the Capital Region of Denmark, Aarhus University, and the Lundbeck Foundation Initiative for Integrative Psychiatric Research.